2021
DOI: 10.3390/diagnostics11112164
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease and Heart Failure–Everyday Diagnostic Challenges

Abstract: Is advanced chronic kidney disease (CKD) a cardiac “no man’s land”? Chronic heart failure (HF) is widely believed to be one of the most serious medical challenges of the 21st century. Moreover, the number of patients with CKD is increasing. To date, patients with estimated glomerular filtration rates <30 mL/min/1.73 m2 have frequently been excluded from large, randomized clinical trials. Although this situation is slowly changing, in everyday practice we continue to struggle with problems that are not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
(113 reference statements)
1
3
0
Order By: Relevance
“…First, our data support the evidence that in the advanced stage of CKD as well as CHF organ-protection afforded by RAS blockade is far from complete [3,4,6,8,9,15,28,29,49], especially when both diseases are combined. Second, our present findings emphasize the difference between organ-protective effects of treatment regimens when initiated immediately after the onset of the damaging insult, and when some degree of CKD and CHF has already beenestablished.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…First, our data support the evidence that in the advanced stage of CKD as well as CHF organ-protection afforded by RAS blockade is far from complete [3,4,6,8,9,15,28,29,49], especially when both diseases are combined. Second, our present findings emphasize the difference between organ-protective effects of treatment regimens when initiated immediately after the onset of the damaging insult, and when some degree of CKD and CHF has already beenestablished.…”
Section: Discussionsupporting
confidence: 81%
“…The incidence and prevalence of chronic kidney disease (CKD) is also increasing [3] and CKD is one of the strongest risk factors for the development of CHF [4,5]. CHF coexists with CKD in approximately half of CHF patients [4][5][6][7][8]. Unfortunately, patients with estimated glomerular filtration rate ≤ 30 ml/min/1.73 m 2 have now largely been excluded from randomized control trials in HF, which limits the information on patients with combined CHF and CKD [4,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic renal dysfunction (eGFR ≤ 60 mL/min/1.73 m 2 ) accelerates HFrEF decompensation and mortality [ 43 , 44 , 45 ]. In patients with sHF with rEF, the elevation of circulating s(P)RR levels was associated with renal dysfunction [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis by Damman et al, CKD was found in approximately half of patients with HF. Other studies have indicated that kidney damage occurred in 43% of patients with chronic HF and in 53% of patients with acute HF [ 19 , 20 , 21 ]. Many studies have also shown that AF increased the risk of CKD, and vice versa [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%